Design And Development Of An ESP32-Based Transporter Robot For Lightweight Goods Using The Arduino IDE - Achmad Hosen Zaini; Wincoko Wincoko; Yanuar Sinatra (International Journal of Health Engineering and Technology, 2026)
This research develops a transporter robot controlled by a wireless joystick for light cargo transportation applications. The system uses the ESP32 microcontroller to process commands from the joystick via a wireless connection, which then controls the DC motor to drive the robot wheels using PWM signals, and a servo motor to operate the gripper that lifts light items up to 300 grams. The robot is equipped with BTS7960 drivers for the DC motors and L293D drivers for the servo motor. The robot’s power source is a 18650 battery, which supports operation for 50-65 minutes. The method used is Research and Development (R&D), focusing on the design, implementation, and testing of the transporter robot. Testing was conducted to evaluate the robot's ability to transport items, movement stability, and response to joystick commands. The test results show the robot can move at a speed of 0.6 m/s and turn with precision. The gripper can lift items up to 280 grams stably, and the robot has a fast joystick response time of less than one second. The contribution of this research is the development of an efficient wireless-controlled transporter robot, with applications in light cargo transportation in confined environments, such as industries and warehouses. The simple and efficient system makes this robot a practical solution for improving operational efficiency in various applications.